Kaznodziejstwo Kacpra Balsama na tle przepowiadania wybranych jezuitów w Rzeczypospolitej epoki saskiej - Wolański, Filip (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny)
Jesuit preaching in the Polish-Lithuanian Commonwealth was an important model for clergy. Each generation of Polish Jesuits had outstanding preachers. In the first half of the 18th century it was Kacper Balsam. He was born in Lviv but became famous for his sermons delivered in Krakow. The article compares the sermons of Balsam and selected Jesuits active at the same time with similar achievements: Konstanty Awedyk, Franciszek Borowski, Jerzy Dębski, and Atanazy Ludwik Kierśnicki. Despite numerous thematic similarities, Balsam stands out.
Keywords: Kacper Balsam